Saturation sensitivity and influencing factors of marine DC resistivity inversion to submarine gas hydrate - Qiu, Ning; Fu, Qicheng; Yang, Liu; Sun, Zhen; Chang, Yanjun; Du, Bingrui (Frontiers in Earth Science, 2022)
The submarine gas hydrate usually exists in the sediment in the continental slope. The bottom simulating reflector (BSR) on the reflected seismic was identified as the bottom of the hydrate stability zone. However, many BSRs may not find the hydrate's effective storage and its underlying free gas in many places. It is essential to identify the saturation of the hydrate. The resistivity can be used to evaluate the hydrate's porosity and saturation. The hydrate boasts a the high resistance to the surrounding sediments. The sensitivity of the marine Direct Current resistivity method (DCR) to the high resistance of the sediment can be used to evaluate the saturation of the hydrate. We have assessed the sensitivity of various DCR array arrangement, towed depths, hydrate thicknesses, and saturation. These influencing factors for improving recognition ability were also systematically analyzed. We have compared the inversion results of various DCR array arrangements, as well as different depths, thicknesses and hydrate saturation, and calculated the saturation. We suggest using the corrected saturation equation to analyze the DCR results, which can improve the ability of hydrate identification. Evaluating these parameters will help develop or select DCR instruments for detecting the submarine gas hydrate.